PWE-064 The Utility of An Enteric Bacterial PCR Panel In Evaluating Patients with Diarrhoea and Raised Faecal Calprotectin. (17th August 2016) - Kumar, S; Taylor, J; Planche, T; Alexakis, C; Soubriere, A; Poullis, A; Pollok, R
Abstract : Introduction: Faecal calprotectin (FCP) assay has an important role in identifying potential cases of inflammatory bowel disease (IBD). However, a significant proportion of patients presenting with diarrhoea and raised FCP do not prove to have IBD following investigation of whom a proportion have an acute self-limiting gut infection. Enteric pathogens are alternative causes of a raised FCP. Alleviating the need for endoscopy in the patients will save money and reduce patient anxiety. However, conventional laboratory methodologies are time consuming and insensitive in detecting gut infection. Commercial nucleic acid amplification test (NAAT) technology now makes it possible to test stool for a panel of gut pathogens quickly and relatively cheaply. In this pilot study, we evaluated this technology in detecting gut infection amongst patients with a diarrhoeal illness and raised FCP, presenting in the community. Methods: Ninety patients with diarrhoea had stool samples submitted from the community to the laboratory for FCP measurement. Samples were anonymised before testing with NAAT (BD MAX™ Enteric Bacterial Panel). The targets of this assay are Salmonella spp., Campylobacter spp. Shigella ( Shigella spp . and enteroinvasive E. coli ) and verotoxigenic E coli . Samples were stratified by FCP level into sub-groups (n = 30): <50, 50–150, >150 µg/g stool and analysed for the presence and type of gut infection found. All samples were also cultured using standard media. Results: 2/30 samples tested (7%, 95% CI 8–23%) with FCP > 150 µg/g tested positive by NAAT for Campylobacter. No patients with FCP below 150 µg/g had a detectable pathogen. No samples were positive by conventional culture methods. Conclusion: This pilot study supports a role for the use of multiplex NAAT in detecting enteric pathogens amongst patients with diarrhoea and raised FCP. Prospective studies are required to evaluate this approach further which offers the potential to refine the IBD referral pathways from primary care and reduce the need for endoscopic and radiological tests. Disclosure of Interest: None Declared